2017
DOI: 10.1021/acs.jpcc.7b02294
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Sodium Dodecyl Sulfate with Lipid Monolayer Studied by Sum-Frequency Generation Spectroscopy at Air–Water Interface

Abstract: We employed vibrational sum-frequency generation (VSFG) spectroscopy to obtain molecular-level understanding of interaction of anionic surfactant sodium dodecyl sulfate (SDS), in low bulk concentration at the micromolar level, with lipid monolayer zwitterionic 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) at the air–water interface. These results are different from those reported at higher bulk concentration of SDS at millimolar level. At very low concentration neither DPPC nor SDS produces any VSFG signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 44 publications
(96 reference statements)
1
21
0
1
Order By: Relevance
“…It has recently been reported that analyzing PPP is beneficial compared to analyzing SSP and PPP polarization combinations because one can avoid difficulties resulting from the CH 3 SS split caused by Fermi interaction with an overtone of the bending mode and interference of the CH vibrational modes with the OH stretch of the interfacial water. 27,64 A range of 30.8−40.5°was found for the average tilt angle (θ) of the terminal methyl group of the alkyl tail. In an all-trans methylene configuration, the difference in tilts between methyl groups and the overall alkyl chain is 41.5°.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…It has recently been reported that analyzing PPP is beneficial compared to analyzing SSP and PPP polarization combinations because one can avoid difficulties resulting from the CH 3 SS split caused by Fermi interaction with an overtone of the bending mode and interference of the CH vibrational modes with the OH stretch of the interfacial water. 27,64 A range of 30.8−40.5°was found for the average tilt angle (θ) of the terminal methyl group of the alkyl tail. In an all-trans methylene configuration, the difference in tilts between methyl groups and the overall alkyl chain is 41.5°.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Mit Erreichen eines Grenzwertes der SDS-Konzentration führen die Va n-der-Waals-Wechselwirkungen (vdW) zwischen den hydrophoben Ketten der SDS-Moleküle zu einer gewissen Ordnung der SDS-Moleküle an der Flüssigkeit/Luft-GF.D ie Methyl-und Methylen-Schwingungen in den SFG-Spektren sind im Einklang mit früheren Studien. [20] Die Existenz des Methylen-Signals (bei 2860 cm À1 )w eist auf gauche-Defekte in der adsorbierten SDS-Schicht hin.…”
Section: Ergebnisse Und Diskussionunclassified
“…Indeed, in recent years, SFG has widely been applied to study the molecular-level interfacial structures between model cell membranes and different drugs, such as peptides, proteins, DNA, nanoparticles, and polymers. Interfacial features, including molecular position, orientation, and conformation after interaction with model cell membranes, can be acquired by analyzing the SFG spectra, which are useful for drug design. For instance, a number of antimicrobial peptides have been studied to understand the mechanism on how the cell membranes are disrupted. , It should be noted that the SFG studies were normally performed with no control of the interfacial flow.…”
Section: Introductionmentioning
confidence: 99%